Mapping geographical inequalities in childhood diarrhoeal morbidity and mortality in low-income and middle-income countries, 2000–17: Analysis for the Global Burden of Disease Study 2017 - Local Burden of Disease Diarrhoea Collaborators (Elsevier, 2022)
This article was published in the Lancet by Elsevier [ © 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license] and the definite version is available at: https://doi.org/10.1016/S0140-6736(20)30114-8 The Journal's website is at: https://www.thelancet.com/journals/lancet/article/PIIS0140-6736(20)30114-8/fulltext?fbclid=IwAR01WJlCIAlaSUfF5j2yYA9JXWVwpWmQxAUps783rd-RBNCwViy-skL7QKo&%20#%20